Fabrication of NiFe2O4/SiO2/TiO2 Magnetic Composite for Effective Photodegradation of Congo Red Dye - Hariani, Poedji Loekitowati; Salni, Salni; Kimur, Melviana Violetta; Hidayati, Nurlisa; Elfita, Elfita (Indonesian Journal of Chemistry, 2025)
This study aims to fabricate a NiFe2O4/SiO2/TiO2 magnetic composite to serve as a photocatalyst for the degradation of Congo red dye. The catalyst characterization involved XRD, FTIR, UV-vis DRS, BET, VSM, SEM-EDS, and pHpzc analyses. The performance in degradation was determined by the effect of various variables, including solution pH, dye concentration, and irradiation time. Results revealed that the NiFe2O4/SiO2/TiO2 composite exhibited a crystallite size of 24.56 nm and a bandgap of 2.1 eV. The surface area of NiFe2O4/SiO2/TiO2 was measured at 154 m2/g, exceeding that of NiFe2O4/SiO2 and NiFe2O4, which were observed at 122 and 51 m2/g, respectively. NiFe2O4/SiO2/TiO2 exhibited magnetic properties with a magnetic saturation of 18.55 emu/g. Under optimal conditions (pH 5, initial dye concentration of 20 mg/L, and 90 min of visible irradiation), the degradation efficiency reached 96.86%. It was concluded that the photodegradation was effective, as its efficiency decreased from 96.86 to 92.45% after five reuse cycles. The presence of mineralization was evaluated using total organic carbon analysis, which revealed an 84.60% reduction in carbon content.